Decoding the Cognitive Engine: How IBM Watson Health Worked and Its Legacy in AI-Driven Medicine - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The promise of Artificial Intelligence AI to revolutionize healthcare is one of the most compelling narratives of the 21st century. At the forefront of this ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation